Multi-omics analysis revealed the differential effects and mechanisms of PFOA and OBS exposure on liver and intestinal function - Minjie Yu; Ruochen Ren; Hongbo Zeng; Meng Hou; Kaiyi Jiang; Caihong Hu; Yingping Xiao; Wentao Lyu (Molecular & Cellular Toxicology, 2026)

Comparison and Optimization of Intermittent Aeration/Interval Aeration for Enhancing Nitrogen Removal in Continuous Flow Anaerobic/Oxic/Anoxic Processes - Ruochen Hu; Zeming An; Yuanqi Gu; Xinjie Gao; Liang Zhang; Yongzhen Peng (Bioresource Technology, 2026)

Investigation on in-situ and ex-situ catalysis of metal salt in biomass photo-thermal pyrolysis: Effects on decoupled primary and secondary reactions - Dexin Huang; Gongxiang Song; Ruochen Li; Kai Xu; Jun Xu; Long Jiang; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Fuel, 2026)

Intrinsic ion migration-induced susceptible two-dimensional phase-transition memristor with ultralow power consumption - Lanhao Qin; Yimeng Yu; Cheng Fang; Yujie Liu; Kaichen Zhu; Decai Ouyang; Shenghong Liu; Bailing Song; Ruochen Zhou; Mario Lanza; Wenhua Hu; Jinsong Wu; et al. (Science Bulletin, 2025)

Inhibition of the canonical Wnt/β-catenin pathway interferes with macropinocytosis to suppress pseudorabies virus proliferation - Chongyang Wang; Ting Wang; Qingrun He; Qili Hou; Liuyuan Duan; Ruochen Hu; Yu Han; Yongchun Yang; Houhui Song; Zengqi Yang (Veterinary Microbiology, 2025)

Bottom-up nucleation induced conformal crystallization for inverted MA-free perovskite solar cells on textured substrates - Ruochen Liu; Jiawei Xu; Tianxiang Hu; Xiang Li; Kongxiang Wang; Qi Huang; Zhongtao Duan; Hong Liu; Weifan Qian; Haiting Zhou; Chunxiao Cong; Xiaofei Yue; et al. (Chemical Engineering Journal, 2025)

Molecular characterization of petroleum acids from diverse geological origins via n-Butylsilane reduction - Haojie Hu; Shuofan Li; Yuanfeng Wang; Ruochen Yang; Jianxun Wu; Weilai Zhang; Chen He; Han Li; Yahe Zhang; Di Zhu; Quan Shi (Fuel, 2024)

Quick measurement method of three components in lignocellulosic biomass based on kinetic mechanism analysis of PT-TGA - Gongxiang Song; Dexin Huang; Aishu Li; Ruochen Li; Song Hu; Kai Xu; Qiangqiang Ren; Hengda Han; Yi Wang; Sheng Su; Jun Xiang (Fuel, 2024)

A DEA-based method of watershed ecological compensation allocation and liability sharing and its application: a case study of the Xin’an River - Feng Yang; Ruochen Hu; Qiong Xia; Dawei Wang (Environment, Development and Sustainability, 2023)

Newcastle disease virus forms inclusion bodies with features of liquid-liquid phase separation - Chongyang Wang; Liuyuan Duan; Ting Wang; Wenbin Wang; Yu Han; Ruochen Hu; Qili Hou; Haijin Liu; Juan Wang; Xinglong Wang; Sa Xiao; Ruyi Dang; et al. (Veterinary Microbiology, 2023)

Genetic and pathogenic characterization of an NADC-34-like isolate of porcine reproductive and respiratory syndrome virus - Yongxin Zhao; Ruiqing Wang; Wei Li; Chenfei Yu; Riteng Zhang; Ruochen Hu; Ruhai Guo; Zengqi Yang; Yefei Zhou; Xinglong Wang (Archives of Virology, 2023)

The increasing contribution of greening to the terrestrial evapotranspiration in China - Genan Wu; Xinchen Lu; Wei Zhao; Ruochen Cao; Wenqi Xie; Liyun Wang; Qiuhong Wang; Jiexuan Song; Shaobo Gao; Shenggong Li; Zhongmin Hu (Ecological Modelling, 2023)

An overall consistent increase of global aridity in 1970–2018 - Dengnan Luo; Zhongmin Hu; Licong Dai; Guolong Hou; Kai Di; Minqi Liang; Ruochen Cao; Xiang Zeng (Journal of Geographical Sciences, 2023)

β-catenin facilitates fowl adenovirus serotype 4 replication through enhancing virus-induced autophagy - Ting Wang; Chongyang Wang; Jinjie Han; Xiaolan Hou; Ruochen Hu; Wenchi Chang; Lizhen Wang; Xuefeng Qi; Jingyu Wang (Veterinary Microbiology, 2023)

The global decline in the sensitivity of vegetation productivity to precipitation from 2001 to 2018 - Xiang Zeng; Zhongmin Hu; Anping Chen; Wenping Yuan; Guolong Hou; Daorui Han; Minqi Liang; Kai Di; Ruochen Cao; Dengnan Luo (Global Change Biology, 2022)
The sensitivity of vegetation productivity to precipitation ( S ppt ) is a key metric for understanding the variations in vegetation productivity under changing precipitation and predicting future changes in ecosystem functions. However, a comprehensive assessment of S ppt over all the global land is lacking. Here, we investigated spatial patterns and temporal changes of S ppt across the global land from 2001 to 2018 with multiple streams of satellite observations. We found consistent spatial patterns of S ppt with different satellite products: S ppt was highest in dry regions while low in humid regions. Grassland and shrubland showed the highest S ppt , and evergreen needle‐leaf forest and wetland showed the lowest. Temporally, S ppt showed a generally declining trend over the past two decades ( p S ppt was especially noticeable in North America and Europe, likely due to the increase in precipitation. In central Russia and Australia, however, S ppt showed an increasing trend. Biome‐wise, most ecosystem types exhibited significant decrease in S ppt , while grassland, evergreen broadleaf forest, and mixed forest showed slight increases or non‐significant changes in S ppt . Our finding of the overall decline in S ppt implies a potential stabilization mechanism for ecosystem productivity under climate change. However, the revealed S ppt increase for some regions and ecosystem types, in particular global grasslands, suggests that grasslands might be increasingly vulnerable to climatic variability with continuing global climate change.

Effect of silicate supplementation on the alleviation of arsenite toxicity in 93-11 (Oryza sativa L. indica) - Haichao Hu; Junting Zhang; Hong Wang; Ruochen Li; Fengshan Pan; Jian Wu; Ying Feng; Yeqing Ying; Qingpo Liu (Environmental Science and Pollution Research, 2013)